The premousterian infantile mandible of Calabria - Stęślicka-Mydlarska, Wanda (Anthropological Review, 1977)
A new mandible of a Neandertal child was found by chance on September 6, 1970 at Archi, near Reggio di Calabria, in Italy. Ascenzi states for the child the sex masculin and the age of 5-6 years, The mandible is highly mineralized and incomplete. The determination of age and sex in skeletal series over time and space must be interpreted very carefully especially for immature individuals in early childhood. A survey of all the anatomical features leads to the conclusion that this mandible possesses the primitive features found in Neandertalians. After Ascenzi the resemblance of this mandible with that of the child of Ehringsdorf, the Gibraltar child and the mandibles of Skhul is striking. Following the opinions of Weidenreich and Piveteau the Proto-Neandertalians from Weimar-Ehringsdorf belonged to a fossil group with typological characters peculiar for Meriterranean regions. The material (table 2) contains 9 mandibles originating from this region. The metrical technique is applied according to G. Kurnik (fig 2). The data presented in table 2 indicate a rather great polymorphism of the investigated mandibles. A characteristic of the assumed Mediterrancan group of Proto-Neandertalians may be verified after careful analysis of craniological materials.